2018
DOI: 10.1007/s11033-018-4151-6
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes positioning around transcriptional start site of tumor suppressor (Rbl2/p130) gene in breast cancer

Abstract: Dynamic positioning of nucleosomes is pivotal in determining level of genes expression especially on or around transcription start site (TSS) of a gene. Purpose of the current study was to determine nucleosome position around TSS of Rbl2/p130. We investigated Rbl2/p130 expression in connection to nucleosome positions around its TSS among breast tumors and their adjacent normal control tissues (ANCT) using micrococcal nuclease (MNAse) digestion assay and ChIP-PCR analysis. Three fold reduced Rbl2/p130 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The DREAM complex represses E2F target gene expression and inhibits cell cycle progression, ultimately causing cell senescence [ 31 ]. RBL2 has been shown to suppress tumour growth in vivo [ 41 ], and downregulation of RBL2 has been reported in a number of cancers [ 42 , 43 , 44 , 45 , 46 ]. In BCa, epigenetic silencing at the RBL2 transcriptional start site has been reported, although the proteins mediating this repression have not been identified [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DREAM complex represses E2F target gene expression and inhibits cell cycle progression, ultimately causing cell senescence [ 31 ]. RBL2 has been shown to suppress tumour growth in vivo [ 41 ], and downregulation of RBL2 has been reported in a number of cancers [ 42 , 43 , 44 , 45 , 46 ]. In BCa, epigenetic silencing at the RBL2 transcriptional start site has been reported, although the proteins mediating this repression have not been identified [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…RBL2 has been shown to suppress tumour growth in vivo [ 41 ], and downregulation of RBL2 has been reported in a number of cancers [ 42 , 43 , 44 , 45 , 46 ]. In BCa, epigenetic silencing at the RBL2 transcriptional start site has been reported, although the proteins mediating this repression have not been identified [ 45 , 46 ]. We found an enrichment of CBX2 at the RBL2 gene promoter, which suggests that CBX2-associated cPRC1 could directly repress RBL2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ensembl also identifies genomic regions with predicted functional roles, including transcription start sites, enhancers, and promoters, or those that are associated with known peptides. These regions are collectively referred to as 'biological regions' or 'peptides' accordingly, and variation in such sites have also been tied to cancer among other diseases (Farman, Iqbal, Azam, & Saeed, 2018;Hua et al, 2018;Rhie et al, 2018).…”
Section: Constructing a Hierarchy Of Feature Representationsmentioning
confidence: 99%
“…By modulating the accessibility of genomic regions to regulatory proteins, it was observed that the packaging of DNA around the histone octamer plays important roles in many biological processes [7,8]. Most studies on nucleosome function have indicated that nucleosomes are involved in chromatin formation [9], antagonistic transcription factors [10,11], and regulating gene expression [12,13].…”
Section: Introductionmentioning
confidence: 99%